Criticism of Mustafa Azami's Critical Thoughts in Study of Hadith - Isnaeni, Ahmad; Susanto, Is; Haqiqi, Abdurrahman Raden Aji (Ulumuna, 2023)
The existence and authenticity of hadith have become two of the most essential objects in the discourse of hadith among Muslims, especially after coming into contact with criticism from Orientalists. This article describes explicitly and criticizes Azami's hadith thought in the hadith debate among Orientalists. This research is an analytical descriptive research based on content analysis. The results reveal that Azami can position himself as a critic of the Western thesis by presenting historical data as a basis for his thoughts. The rhythm of the scientific debate modeled on by Western thinkers can be dived into and followed convincingly so that their responses and criticisms reach the Orientalists. Orientalists believe that Azami's criticism has not been able to divert the orientation of the general thesis that hadiths are not historically authentic. Azami's defense still needs convincing, and the arguments are still circular. This model of thinking has yet to satisfy the scientific desires of the Orientalists, so it has a small implications.